2004
DOI: 10.24278/2178-5031.2004162461
|View full text |Cite
|
Sign up to set email alerts
|

Pteridófitas Do Parque Estadual De Vassununga, Santa Rita Do Passa Quatro (Sp), Brasil. Gleba Pé-De-Gigante

Abstract: Neste trabalho foi realizado um levantamento de pteridófitas na Gleba Pé-de-Gigante do Parque Estadual de Vassununga, localizado no município de Santa Rita do Passa Quatro, sob as coordenadas 21º36’39,01054’’S e 47º37’03,46727’’W. As coletas foram realizadas em três trilhas, denominadas Trilha do Meliponário, Trilha do Córrego Paulicéia e Trilha da Torre. Foram reconhecidas 15 espécies de pteridófitas pertencentes a 7 famílias. Dessas, as mais representativas foram Polypodiaceae e Thelypteridaceae com quatro e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…1), predominantly in the understory, where pteridophytes occupy several microenvironments. A predominance of pteridophytes in wet forests (Mata de galeria and Mata cCiliar) has been reported in other studies in the Cerrado (Colli et al 2004;Fernandes et al 2022;Kreutz et al 2016;Miguez et al 2013;Nunes & Labiak 2021). Compared to those studies, the species number reported here is relatively low, considering the expanded size of the EESGT.…”
Section: Pteridophyte Occurrence In Different Habitats Within the Eesgtsupporting
confidence: 45%
See 1 more Smart Citation
“…1), predominantly in the understory, where pteridophytes occupy several microenvironments. A predominance of pteridophytes in wet forests (Mata de galeria and Mata cCiliar) has been reported in other studies in the Cerrado (Colli et al 2004;Fernandes et al 2022;Kreutz et al 2016;Miguez et al 2013;Nunes & Labiak 2021). Compared to those studies, the species number reported here is relatively low, considering the expanded size of the EESGT.…”
Section: Pteridophyte Occurrence In Different Habitats Within the Eesgtsupporting
confidence: 45%
“…The lower species richness in the Cerrado, which is dominated by open habitats under a seasonally dry climate, reflects the ecological preference of most pteridophyte groups for moist and forested areas. Nevertheless, many species can be found in wet environments associated with water bodies, such as gallery forests and swamps (Colli et al 2004;Fernandes et al 2022;Kreutz et al 2016;Miguez et al 2013;Nunes & Labiak 2021). On the other hand, some dry-adapted lineages have successfully colonized open habitats of the Cerrado, such as species of Anemia (Hietz 2010;Mickel 2016), a genus especially diverse in Central Brazil (Mickel 2016).…”
Section: Introductionmentioning
confidence: 99%